USE OF ABBREVIATION IN INTERNET FORUMS - Sirazetdinova Liliya Alimdzhanovna (Galaxy International Interdisciplinary Research Journal, 2022)
The paper describes the varieties of abbreviations and other abbreviations used in the speech of Internet forums, their functions and features of use are considered. The author reveals the connection between the active use of abbreviations of one kind or another and their functions in Internet speech.